The Role of the English Language in the Formation of Creative Activity of Students in Primary Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is currently psychologists trying to direct the active independent creative activity of students in the educational process to the activity of independent knowledge, independent acquisition of knowledge. Maximizing students' cognitive activity and developing their independent creative thinking is becoming an important task of school education.